Efeitos de inseticidas biológicos (óleo de nim, Azadirachta indica, e entomopatógenos Metarhizium anisopliae e Beauveria bassiana) sobre a cigarrinha-das-raízes, Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae), em cana-de-açúcar sob cultivo orgânico, em relação à mortalidade natural - Baptistussi, Roberta Carrara (Universidade Federal de São Carlos, 2010)
The neem oil obtained from the Azadirachta indica plant, plus formulations containing the fungus Beauveria bassiana and Metharizium anisopliae, were used to control the spittlebug Mahanarva fimbriolata in organic cultivation of sugarcane. The action of these products was compared with natural mortality of the insect, through parcels without use of any products. The experiment was conducted at Santo Antônio Plant in Sertãozinho-SP, in variety RB 85 5536 in the period from March to May 2008. It was employed the statistical design of subdivided parcels, with seven treatments, three repetitions and four periods. It wasn t observed significant statistical differences between the treatments studied either generally or in different periods evaluated. The natural mortality ranged from 55,5% to 80,81% suggesting that the action of environmental agents was sufficient, it laid off any kind of products, even the alternative.
Effects of biological insecticides (neem oil, Azadirachtina indica and entomopathogenic Metharizium anisopliae and Beauveria bassiana) about spittlebug Mahanarva fimbriolata (Hemiptera:cercopidae) in organic sugarcane in relation to natural mortality
Keywords: Cana-de-açúcar; Azadirachta indica; Entomopatógenos; Efeitos ambientais; Óleo de nim; Temperatura; Chuva; Neem oil; Entomopathogenic; Temperature; Rain; CIENCIAS AGRARIAS